Multibit Ferroelectric FET Based on Nonidentical Double HfZrO2 for High-Density Nonvolatile Memory - Liao, C.-Y.; Hsiang, K.-Y.; Hsieh, F.-C.; Chiang, S.-H.; Chang, S.-H.; Liu, J.-H.; Lou, C.-F.; Lin, C.-Y.; Chen, T.-C.; Chang, C.-S.; Lee, M. H. (IEEE electron device letters, 2021)
A double-HZO (HfZrO 2 ) FeFET (ferroelectric FET) with nonidentical ferroelectric thicknesses is experimentally demonstrated with as low as \vert {V}_{P/E}\vert = {5} V, 2-bit endurance > 10 5 cycles and retention > 10 4 s. Inserting an insulator to separate the ferroelectric layers and avoid the monoclinic formation of a thick Fe-HZO (ferroelectric-HZO) is a useful method to enhance the MW (memory window) for MLC (multilevel cell) applications. Double-HZO has a lower ER (error rate) and shows a 600X improvement compared to single-HZO. The stacked HZO FeFET has potential as an MLC for high-density NVM (nonvolatile memory) applications.